From Taboo to Negotiated Tradition: Marriage During Muharram in Gunungkidul within Islamic Family Law Context - Muhammad Royhan Assaiq; Siti Muna Hayati; Agus Suprianto; Ibnu Aqil; Hanin Yumna (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study addresses the gap between normative Islamic legal perspectives, which deny any prohibition of marriage in certain months, and socio-cultural practices that maintain marriage taboos in Javanese society. It aims to explain how Javanese traditions interpret marriage during the month of Muharram and to identify the factors that drive the negotiation of this taboo. This research is a field study with a qualitative socio-legal approach conducted in Gunungkidul Regency. Data were collected through in-depth interviews with ten informants, including six individuals who married during Muharram, two marriage guardians, and two officials from the Office of Religious Affairs. Data were analyzed using the Miles and Huberman model and interpreted through Bronfenbrenner’s ecological systems theory. The findings reveal that decisions to marry during Muharram are influenced by practical family considerations, religious understanding, and institutional legitimacy. These factors indicate that the Muharram marriage taboo has not disappeared but has been reinterpreted as a negotiable cultural practice. Theoretically, this study contributes to Islamic family law by demonstrating that legal norms interact dynamically with social and cultural systems, in which local traditions may function as ‘urf that is continuously negotiated within the framework of Islamic law. Therefore, this study recommends strengthening context-based Islamic legal education grounded in maqāṣid al-sharī‘ah to distinguish between normative religious teachings and culturally constructed beliefs.